Зі спогадів - Уманцев, Ф. (Студії мистецтвознавчі, 2007)
More than a similar project. Within the time that has passed we can notice the ancient methodology which has been much changed lateky, facts which need to be precised and completed and the whole conception which has to be revised. But it is impossible to deny the fact this fundamental work has become a study book for several generations of Ukrainian scientists. The point of creation of new history, revision of the national art heritage within the nowadays realities is very actual.